The digital negative : raw image processing in Lightroom, Camera Raw, and Photoshop - Schewe, Jeff (Peachpit Press, 2016)
"Shooting in the raw format gives digital photographers complete control over every aspect of image quality. The Digital Negative is devoted exclusively to the topic and shows you how to make the most of that control to extract the best-possible raw rendering of your digital negatives and to use Photoshop to achieve the highest quality in your images."--Provided by publisher.